Program Bimbingan Konseling Perilaku Etis siswa SMP - Siti Rahmawati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Islamic guidance and counseling is an effort to help individuals learn to develop faith-fitrah or return to faith-fitrah. Ethical behavior can act as behavior or rules of behavior to produce the best behavior. The purpose of writing in this journal is to find out the ideal ethical behavior guidance program for Junior High School (SMP) level, to know the guidance services provided and the evaluation techniques and infrastructure needed in implementing the ethical behavior guidance program in Junior High School. in this study is a qualitative method, the goal is that the data that has been received by researchers, both primary data and secondary data can be analyzed more deeply. Data collection techniques using observation, documentation, and interview techniques. The results of the research obtained are the creation of an ideal ethical behavior guidance program that can be applied to junior high schools. This counseling guidance program is able to help junior high schools to provide guidance to students so that they can create students who are civilized and have noble character. Keywords: Counseling Guidance, Ethical Behavior; Middle School Students